2015
DOI: 10.1007/s12011-015-0458-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and the Underlying Mechanism of T Cells in Thymus of Mice by Oral Administration of Sodium Fluoride

Abstract: The underlying mechanism of thymic T cell regulation has been a hot topic of research in recent years. Fluoride is toxic at high concentrations and fluoride toxicity to thymic T cells was assessed in our study. To explore T cell responses to excess fluoride, different concentrations of fluoride were uptake by mice for 6 weeks. The expression of genes, including Foxn1, Cbx4, DLL4, and IL-7 gene, associated with the development and differentiation of T cells in thymic epithelial cells(TECs) was lower in the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…In our previous study, we found that high fluoride levels can reduce IL-2, IL-4, IL-6, TNF-α and IFN-γ in the cecal tonsil, and intestines of broiler chickens [ 14 ], and that NaF can reduce the percentages of CD3 + , CD3 + CD4 + , CD3 + CD8 + T lymphocytes and CD19 + B lymphocytes and of IL-2, TNF-α, IFN-γ, TGF-β expression levels in cultured splenic lymphocytes of mice [ 36 ]. Our findings are consistent with the report of Yin et al [ 43 ] that high fluoride decreased the percentages of thymic CD4 + , CD8 + T cells and IL-2, IL-10 mRNA expression in mice. Also, Fentue et al [ 19 ] reported that NaF decreased IL-10 mRNA expression level in murine macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study, we found that high fluoride levels can reduce IL-2, IL-4, IL-6, TNF-α and IFN-γ in the cecal tonsil, and intestines of broiler chickens [ 14 ], and that NaF can reduce the percentages of CD3 + , CD3 + CD4 + , CD3 + CD8 + T lymphocytes and CD19 + B lymphocytes and of IL-2, TNF-α, IFN-γ, TGF-β expression levels in cultured splenic lymphocytes of mice [ 36 ]. Our findings are consistent with the report of Yin et al [ 43 ] that high fluoride decreased the percentages of thymic CD4 + , CD8 + T cells and IL-2, IL-10 mRNA expression in mice. Also, Fentue et al [ 19 ] reported that NaF decreased IL-10 mRNA expression level in murine macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that NaF can suppress the cellular immunity in mice and Th2 cytokines, including IL-4, IL-6, and IL-10, and Th17 cytokine (IL-17A) contents were decreased after exposed to NaF in excess of 12 mg/kg. 31 In addition, our findings are consistent with some reports that high fluoride decreased the percentages of thymic CD4+ and CD8+T cells and IL-2 and IL-10 mRNA expression in mice, 35 and at the cellular level, high NaF concentrations (20 and 50 mg/L) significantly reduced the secretion of TNFα, IL-2, IL-6, and IL-1β in the supernatant. 33 Therefore, we speculate that NaF affects the inflammation and immune response of rat heart tissue by affecting factors such as IL-6 and IL-10.…”
Section: ■ Discussionsupporting
confidence: 92%
“…Fluoride induces the apoptosis of thymus cells and leads to immunosuppression; additionally, high concentrations of fluoride damages thymic epithelial cells (TECs) by altering the expression of T cell function–related genes and the production of immunomodulatory cytokines ( 45 ). In TECs, the expression of the Foxn1 , Cbx4 , DLL4 , and IL-7 genes related to T cell development and differentiation are reduced ( 46 ).…”
Section: Effects Of Fluoride On Immune Organsmentioning
confidence: 99%